Business taxes and the electoral cycle - Dirk Foremny; Nadine Riedel (Center for Economic Studies and ifo Institute (CESifo), 2012)
The purpose of this paper is to assess whether politicians manipulate the timing of tax rate changes in a strategic way to maximize reelection prospects. To do so, we exploit the German local business tax as a testing ground which is set autonomously by German municipalities. As election dates vary across local councils, the data allows us to disentangle effects related to the timing of elections from common trends. Using a rich panel data-set for German municipalities, we assess the impact of elections on local business tax choices. The findings support the notion of a political cycle in tax setting behavior as the growth rate of the local business tax is significantly reduced in the election year and the year prior to the election, while it jumps up in the year after the election. This pattern turns out to be robust against a number of sensitivity checks.
Keywords: H25; H71; D72; 330; business tax choice; political economy; election cycle; Gewerbesteuer; Gemeindesteuer; Steuerpolitik; Wiederwahl; Politischer Konjunkturzyklus; Schätzung; Deutschland